The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1039/c6mt00125d
|View full text |Cite
|
Sign up to set email alerts
|

Iron accumulates in the primate choroid of the eye with aging as revealed with synchrotron X-ray fluorescence microscopy

Abstract: Aging leads to an increase in iron-loaded cellular structures in the choroid of the eye. This study was carried out to determine the distribution and content of iron, zinc and copper in the macular retina, choroid and retrobulbar optic nerve of young (4-5 years, n = 3) and aged (15-16 years, n = 5) male non-human primates, Macaca fascicularis, whose ocular anatomy is similar to humans. Thirty μm-thick tissue sections were analysed with synchrotron X-ray fluorescence and stained histologically for iron depositi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 27 publications
(32 reference statements)
0
5
0
Order By: Relevance
“…However, it is striking that the aged choroid is able to accumulate iron selectively in focal regions where the iron fluorescence intensity ranges from 2- to 7-fold (1002–3752 ppm) the mean level in the rest of the choroidal stroma (500 ppm) and maximum iron levels in blood vessel lumina (596 ppm). As shown in Ugarte et al 2016 , iron hotspots with iron ppm > 1000 increased in number (young 4–8 vs. aged 1–93 per area scanned) and size (< 2–13 μm in young animals vs. < 2–22 μm in aged) with age.
Fig.
…”
Section: Resultsmentioning
confidence: 57%
See 2 more Smart Citations
“…However, it is striking that the aged choroid is able to accumulate iron selectively in focal regions where the iron fluorescence intensity ranges from 2- to 7-fold (1002–3752 ppm) the mean level in the rest of the choroidal stroma (500 ppm) and maximum iron levels in blood vessel lumina (596 ppm). As shown in Ugarte et al 2016 , iron hotspots with iron ppm > 1000 increased in number (young 4–8 vs. aged 1–93 per area scanned) and size (< 2–13 μm in young animals vs. < 2–22 μm in aged) with age.
Fig.
…”
Section: Resultsmentioning
confidence: 57%
“…The content and distribution of iron in the retina and choroid have been analysed in relation to ageing and age-related macular degeneration (AMD), the most common blinding condition in the population over the age of 50 (Stevens et al 2013 ). We recently demonstrated that iron-rich deposits accumulate in the non-human primate choroid with age (Ugarte et al 2016 ). Other groups have described accumulation of iron in Bruch’s membrane and retinal pigment epithelial cells in donor eyes with AMD using histochemical methods and analytical electron microscopy (Biesemeier et al 2015 ; Hahn et al 2003 ; Wong et al 2007 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For the excitation energy of 17 keV the following sensitivities were obtained: 8 counts s À1 fg À1 for Ca K to 249 counts s À1 fg À1 for As K. The lower limits of detection ranged from 169 ag (Ca) to 4 ag (As) in 1000 s. For 12 keV, sensitivities obtained ranged from about 23 counts s À1 fg À1 for Ca K to 396 counts s À1 fg À1 for Zn K. detection limits presented do not reach the impressive values of the P06 beamline at PETRA III (due to the considerably lower flux) and of ID16B-NA at ESRF (due to the larger beam size), the setup is very recommendable for imaging biological samples, which we have illustrated by means of scans on a bone sample and a single cancer cell. Additionally, it should be mentioned that at Diamond Light Source there exists the possibility to first scan a larger sample area at I18 with micrometer resolution (for example 2 Â 2 mm) followed by further investigation of smaller areas of interest with submicrometer resolution at B16 (Ugarte et al, 2016). In conclusion, the XRF setup on the B16 beamline is very well suited for studying thin samples and especially for biological applications.…”
Section: Resultsmentioning
confidence: 98%
“…Therefore, submicro-beam would be a perfect choice, allowing measurements of such structures and, moreover, allowing resolving of substructures, such as cement lines in bone (several micrometers thick). To find the ideal SR-XRF imaging method for the investigation of trace element distributions and possible substructures (in the micrometer range) in biological samples, such as bone, single cells and other tissues (Ugarte et al, 2016;Mihucz et al, 2016), SR-XRF at the B16 beamline at Diamond Light Source was tested with different samples and standards. Test measurements were performed with two different excitation energies, 12.7 and 17 keV.…”
Section: Introductionmentioning
confidence: 99%